Analisis Laporan Audit Kinerja Pengelolaan Piutang Jangka Panjang di LKPP Tahun 2023 - Aulia Hilda Pertiwi; Oman Rusmana (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2025)
Performance audit reports are an important instrument in assessing the effectiveness of resource management by government agencies. This article analyzes the results of the performance audit of long-term receivables management at the Government Goods/Services Procurement Policy Agency (LKPP) in 2023. The purpose of this study is to identify weaknesses and opportunities for improvement in the receivables management process. Using a qualitative descriptive approach based on secondary data from the audit report of the Audit Board of Indonesia (BPK), several major problems were found, including weaknesses in the information system, weak handling of problematic receivables, and inconsistencies in recording between units. The results of the analysis provide recommendations to improve the effectiveness and efficiency of long-term receivables management at LKPP